Underreporting of energy intake in weight loss maintainers. Issue 1 (19th March 2021) - Dahle, Jared H; Ostendorf, Danielle M; Zaman, Adnin; Pan, Zhaoxing; Melanson, Edward L; Catenacci, Victoria A
ABSTRACT: Background: Individuals with overweight or obesity commonly underreport energy intake (EI), but it is unknown if the tendency to underreport persists in formerly obese individuals who lose significant weight and maintain their weight loss over long periods of time. Objective: Assess the accuracy of self-reported EI in successful weight loss maintainers (WLM) compared with controls of normal body weight (NC) and controls with overweight/obesity (OC). Methods: Participants for this case-controlled study were recruited in 3 groups: WLM [ n = 26, BMI (in kg/m 2 ) 24.1 ± 2.3; maintaining ≥13.6 kg weight loss for ≥1 y], NC ( n = 33, BMI 22.7 ± 1.9; similar to current BMI of WLM), and OC ( n = 32, BMI 34.0 ± 4.6; similar to pre–weight loss BMI of WLM). Total daily energy expenditure (TDEE) was measured over 7 d using the doubly labeled water (DLW) method, and self-reported EI was concurrently measured from 3-d diet diaries. DLW TDEE and self-reported EI were compared to determine accuracy of self-reported EI. Results: WLM underreported EI (median, interquartile range) (–605, –915 to –314 kcal/d) to a greater degree than NC (–308, –471 to –68 kcal/d; P < 0.01) but not more than OC (–310, –970 to 18 kcal/d; P = 0.21). WLM also showed a greater degree of relative underreporting (–25.3%, –32.9% to –12.5%) compared with NC (–14.3%, –19.6% to –3.1%; P = 0.02) but not OC (–11.2%, –34.1% to –0.7%; P = 0.16). A greater proportion of WLM was classified as underreporters (30.8%) than NC (9.1%; P = 0.05) but not OC (28.1%; P = 1.00). Conclusions: WLM underreported EI in both absolute and relative terms to a greater extent than NC but not OC. These findings call into question the accuracy of self-reported EI in WLM published in previous studies and align with recent data suggesting that WLM rely less on chronic EI restriction and more on high levels of physical activity to maintain weight loss. This trial was registered at clinicaltrials.gov as NCT03422380.